Cloning, nucleotide sequence, and expression of the plasmid-encoded genes for the two-component 2-halobenzoate 1,2-dioxygenase from Pseudomonas cepacia 2CBS. - Haak, B (1995)
The two-component nonheme iron dioxygenase system 2-halobenzoate 1,2-dioxygenase from Pseudomonas cepacia 2CBS catalyzes the double hydroxylation of 2-halobenzoates with concomitant release of halogenide and carbon dioxide, yielding catechol. The gene cluster encoding this enzyme, cbdABC, was localized on a 70-kbp conjugative plasmid designated pBAH1. The nucleotide sequences of cbdABC and flanking regions were determined. In the deduced amino acid sequence of the large subunit of the terminal oxygenase component (CbdA), a conserved motif proposed to bind the Rieske-type [2Fe-2S] cluster was identified. In the NADH:acceptor reductase component (CbdC), a putative binding site for a chloroplast-type [2Fe-2S] center and possible flavin adenine dinucleotide- and NAD-binding domains were identified. The cbdABC sequences show significant homology to benABC, which encode benzoate 1,2-dioxygenase from Acinetobacter calcoaceticus (52% identity at the deduced amino acid level), and to xylXYZ, which encode toluate 1,2-dioxygenase from Pseudomonas putida mt-2 (51% amino acid identity). Recombinant pkT231 harboring cbdABC and flanking regions complemented a plasmid-free mutant of wild-type P. cepacia 2CBS for growth on 2-chlorobenzoate, and it also allowed recombinant P. putida KT2440 to metabolize 2-chlorobenzoate. Functional NADH:acceptor reductase and oxygenase components of 2-halobenzoate 1,2-dioxygenase were enriched from recombinant Pseudomonas clones.